2022
DOI: 10.7759/cureus.31483
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Rehabilitation and Cardiopulmonary Fitness in Children and Young Adults With Congenital Heart Diseases: A Critically Appraised Topic

Abstract: Public health guidelines and a myriad of studies have proven that exercise is beneficial in the alleviation of various cardio-metabolic diseases. Congenital heart disease (ConHD) is one of the most frequently occurring congenital structural malfunctions in the pediatric population, affecting nine of every 1,000 live births. Only a few studies have established the impact of a structured exercise program on cardiopulmonary fitness in diverse groups of patients with ConHD. It is also alarming to know that a subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…Not only does exercise play important role in maintenance of health wellness, it prevents disease development and progression (Awosika et al, 2022;Uzochukwu et al, 2023). Many studies that reported the roles of exercise in healthy and diseased subjects were conducted in the daytime.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Not only does exercise play important role in maintenance of health wellness, it prevents disease development and progression (Awosika et al, 2022;Uzochukwu et al, 2023). Many studies that reported the roles of exercise in healthy and diseased subjects were conducted in the daytime.…”
Section: Discussionmentioning
confidence: 99%
“…Blood pressure was measured from the arm, an inch above the elbow using Omron BP7000 Evolve Wireless Upper Arm Sphygmomanometer (Iris Global Care, China). Baseline readings were taken at sitting position as previously reported (Okeke et al, 2023;Adeniyi et al, 2021). Blood pressure measurements were also obtained for each of the legs at the first perception of exertion.…”
Section: Measurement Of Blood Pressurementioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the Western diet, which is rich in saturated fats, sucrose, and fructose, together with excessive alcohol consumption, appears to aggravate salt-sensitive fluctuations in BP [37,63]. Identifying the potential mechanisms of salt sensitivity in vulnerable populations and connecting them to protective or beneficial dietary, lifestyle factors, and cardiac rehabilitation exercises can lead to more precise strategies for the prevention of HTN and related complications such as CVD [62,64]. According to current guidelines from the American Heart Association and the American College of Cardiology Foundation, lifestyle modifications are considered a class 1b recommendation for individuals at high to moderate risk for developing CVD [65].…”
Section: Figurementioning
confidence: 99%